Investment Decision on an Issuer in the Capital Market Based on Financial Literature, Minimum Capital, and Fear of Missing Out (FOMO): A Case Study of Trader Community - Prasaja, Disma; Kurniawan, Muhammad Sani; Fatmawati, Inayatullah (PT. LITERASI SAINS NUSANTARA, 2023)
This research aims to determine investment decisions based on financial literature, minimum capital and Fear of Missing Out (FOMO). This research uses quantitative research with data collection techniques through questionnaires distributed to members of the trader group community. Using a purposive sampling technique, the sample taken in this research was 100 investor group members. The data analysis method in this research uses Smart Partial Least Square version 4.0 The results of this research show that Financial Literature has a significant influence on Investment Decisions, Minimum Capital does not significantly influence Investment Decisions and Fear of Missing Out has an influence on Investment Decisions.